2005
DOI: 10.1007/s00268-005-7761-9
|View full text |Cite
|
Sign up to set email alerts
|

Number of Lymph Node Metastases Is a Significant Prognostic Factor in Intrahepatic Cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (IHCC) is a rare primary hepatic tumor. Outcomes after resection and the use of lymph node dissection have not been well described. From a prospective database, we identified 53 patients with IHCC who underwent exploration between April 1983 and March 2004. Hepatic resection was performed in 44 patients, 30 of whom underwent lymph node dissection. Clinicopathological features and outcomes were analyzed. The actuarial 1-year survival was 66.2% in resected patients, compared to 0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
149
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(172 citation statements)
references
References 28 publications
20
149
2
1
Order By: Relevance
“…However, this feature has been shown to have no survival impact and that omitting it actually improved the accuracy of staging. 27 Third, no attempt was made to further stratify Nþ patients according to the number of invaded LNs 28 or the LN ratio 29 because of the lack of standardization of LN harvesting. Finally, our strict inclusion criteria (complete clinical and pathological data sets and proven R0 resection) resulted in 69% of our patients being excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, this feature has been shown to have no survival impact and that omitting it actually improved the accuracy of staging. 27 Third, no attempt was made to further stratify Nþ patients according to the number of invaded LNs 28 or the LN ratio 29 because of the lack of standardization of LN harvesting. Finally, our strict inclusion criteria (complete clinical and pathological data sets and proven R0 resection) resulted in 69% of our patients being excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al [35] recommended systematic LN dissection combined with hepatectomy for mass-forming type IHCC with only a single LN metastasis. Nakagawa et al [37] concluded that the indication for curative resection with systematic LN dissection was no more than two LN metastatic nodules. Consequently, it has been strongly suggested that this so-called systematic LN dissection is merely LN sampling under these circumstances, even if the extended systematic LN dissection had some prognostic meaning in a few previous reports regarding long-term survivors with LN metastasis.…”
Section: Ln Dissection In the Literaturementioning
confidence: 99%
“…1,64,65 Half of our cases of fibrolamellar carcinoma had lymph node metastases compared with only 1 of 62 cases of hepatocellular carcinoma. Cholangiocarcinomas 66,67 and hepatoblastomas 68 also show higher rates of lymph node metastasis at surgery than hepatocellular carcinoma, suggesting a link between these tumors and fibrolamellar carcinomas. However, as our study and many others only include patients who underwent surgical resection, this does not accurately represent the rate of lymph node metastasis at presentation for these various tumors.…”
mentioning
confidence: 99%